Pengaruh Gender Diversity Dan Remunerasi Direksi Terhadap Kinerja Perusahaan Dengan Visibilitas Publik Sebagai Variabel Moderasi - Winda Septiani; Reni Oktavia; Liza Alvia; Widya Rizki Eka Putri (Journal on Education, 2024)
The purpose of this study is to examine the effect of Gender Diversity and Directors' Remuneration in improving firm performance and test whether the Public Visibility of company can strengthen Gender Diversity and Directors' Remuneration on firm performance. The population in this study is state-owned companies listed on the IDX in 2018-2022. By using puposive sampling, 26 companies were selected as samples. The data analysis technique in this study is multiple linear regression analysis. In this study, Gender Diversity is measured by the percentage of female board of directors, Directors’ Remuneration is measured by ratio between remuneration and NBT, Public Visibility is measured by GSV (Google Search Volume). In the other hand, Firm Performance is measured by ROE (Return On Equity). The results prove that Gender Diversity and Directors' Remuneration have a negative effect on firm performance. However, the presence of Public Visibility as a moderating variable can strengthen can strengthen the relationship between Gender Diversity and Directors' Remuneration to Firm Performance. In other words, the higher the Gender Diversity and Remuneration of the Board of Directors balanced with high Public Visibility will be followed by an increase in Firm Performance.